Proceedings of the seventh international conference on tropical bees: Management and diversity and fith Asian apicultural association conference : (International Bee Research Association, 2000)
The aim of the conference is to bring together the international scientific community involved in the study of tropical bees. The conference is not just a gathering of the world's finest mind sharing the latest information on the science of honeybees,...